STAGES OF DRAWING UP A MATHEMATICAL MODEL OF THE ECONOMIC ISSUE - Khalilov Murodiljon Durbek ugli (Modern American Journals, 2026)
The article presents the concept of a mathematical model and the stages of drawing up a mathematical model of an economic issue.
Keywords: Economy, mathematical model, sequence, compound interest, continuous interest.